A logical foundation for logic programming II: Semantics of general logic programs - Bochman, Alexander (The journal of logic programming, 1998)
We suggested in Part I of this study a general logical formalism for Logic Programming based on a four-valued inference. In this paper we give a uniform representation of various semantics for logic programs based on this formalism. The main conclusion from this representation is that the distinction between these semantics can be largely attributed to the difference in their underlying (monotonic) logical systems. Moreover, in most cases the difference can even be reduced to that of the language, that is, to the difference in the logical connectives allowed for representing derivable information.